The Effectiveness of the Science Experimental Guidebook on the Conceptual Understanding of Students with Learning Disabilities - Tülay Şenel Çoruhlu; Murat Pehlevan (Journal of Science Learning, 2021)
This study aimed to develop a science experiments guidebook (based on discussion method and enriched worksheet) for fourth grade mainstreamed students with learning disabilities and to investigate its effect on their conceptual understanding of the "Matter and its Nature", "Living Things and Life", "Physical Events" and "Earth and The Universe" learning domains. Furthermore, mixtures, sieving, filtration, magnetism (Matter and its Nature), recycling (Living Things and Life), simple electrical circuit (Physical Events), and fossil (Earth and The Universe) concepts/issues were determined. Since the aim is to investigate the conceptual understanding of five 4th grade students with learning disabilities, the case study method was used. Conceptual understanding tests, drawing tests, and semi-structured interviews were used as data collection tools. The science experiments guidebook was presented to the students in worksheet format. Besides, worksheets were enriched with avatar images, mobile applications (QR codes), hands-on experiments, and active learning techniques (brainstorming, buzz 22, aquarium, and snowball). As a result of the research, it can be said that the science experiments guidebook had a positive effect on the conceptual understanding of students with learning disabilities.